The Effectiveness of Leadership Styles with Worker Characteristics in Building Construction Projects in the Surabaya Area - Kurniawan, Moch Bambang; Roy Sumaryono; Emmywati (Asian Journal of Multidisciplinary Research, 2026)
This study aims to explore the effectiveness of leadership styles within the context of building construction projects in Surabaya, considering the characteristics of the workers involved. The background of this research is based on the importance of leadership in managing human resources in complex and dynamic construction projects. This study adopts a descriptive qualitative approach, using data collection techniques such as in-depth interviews, field observations, and documentation. The findings indicate that the effectiveness of leadership styles heavily depends on the alignment between the applied leadership style and the characteristics of the workers on-site. Transformational leadership is effective in motivating result-oriented and experienced workers, while an authoritarian style is more appropriate for new workers who require clear direction. Participative leadership is considered effective in enhancing workers' loyalty and engagement in the work process.